PENGARUHIPEMBERIANIAIRIREBUSAN DAUNICINCAUIHIJAU (CycleaIBarbataIMiers)ITERHADAP PENURUNAN TEKANAN DARAHIPADA IBU HAMIL PENDERITAIHIPERTENSI DIKLINIK PRATAMA H.TANJUNG DELI TUAI KABUPATENIDELI SERDANG TAHUNI2025 - Erlina . Hayati; Husna Sari (JURNAL ILMIAH DHDT - KEBIDANAN, 2026)
Pregnant women's hypertension is a major contributing factor to Indonesia's high maternal mortality rate (MMR). One of the new non-pharmacological alternatives is the use of traditional herbal remedies, such as green grass jelly leaves (Cyclea barbata Miers), which are known to contain flavonoids, polyphenols, and calcium with antihypertensive properties. This study sought to see whether boiling green grass jelly leaf water may reduce hypertensive pregnant women's blood pressure. The purpose of this study was to find out if a green grass jelly leaf decoction could lower blood pressure in expectant mothers. The study was carried out at Klinik Pratama H. Tanjung, which is situated in Deli Tua Subdistrict, Deli Serdang Regency, between March and May of 2025. Using a complete sampling technique, 15 pregnant women with a diagnosis of hypertension took part in the study. Blood pressure was taken both before and after the intervention in this study, which used a pre-experimental one-group pretest-posttest design. For five days in a row, 200 millilitres of boiled green grass jelly leaf water were given every morning as part of the intervention. A blood pressure monitoring sheet and a sphygmomanometer were among the tools utilised. The data showed that the average diastolic blood pressure decreased from 94 mmHg to 84 mmHg and the average systolic blood pressure decreased from 146 mmHg to 134 mmHg. A statistically significant effect (p < 0.05) was found in the Wilcoxon test findings, with p = 0.001 for systolic and p = 0.002 for diastolic pressure. When pregnant women with hypertension drink cooked green grass jelly leaf water, their blood pressure dramatically drops. When it comes to treating hypertension during pregnancy, this treatment might be a secure and useful adjunct.